POLITICAL REPRESSIONS AGAINST THE EMPLOYEES OF THE PROSECUTOR’S OFFICE OF KARAKALPAKSTAN IN THE 1930-1940 YEARS: HISTORICAL RESEARCH AND ANALYSIS OF FATE (TAMADDUN NURI JURNALI, 2025)
The article highlights the history of political repressions against prosecution personnel in Karakalpakstan during the 1930s–1940s, their consequences, and the measures being taken to restore historical justice. Based on published books, investigative materials, and biographical data, the study examines the fates of law enforcement officers who became victims of repression. The research focuses on analyzing the mechanisms of political pressure within the prosecution system and their legal implications.